Pengaruh Kompensasi Terhadap Kinerja Pegawai Pada Dinas Perhubungan Kabupaten Bima - Sri Aryani Wati; Muhammad Yusuf; Mukhlis Mukhlis (Universitas 45 Surabaya, 2023)
According to Kasmir (2019) performance is the result of work and actions achieved by fulfilling the tasks and responsibilities given within a certain time, while according to Efandi (2021) performance is the willingness of a person or group of people to carry out or improve activities in accordance with their responsibilities with the desired results. expected. According to W Enny, (2019) it is a difficult and very important skill for a supervisor. It can be concluded that performance is an activity that carries out its functions in accordance with its responsibilities and has difficult and very important skills. According to Sedarmayati (2018) Employee performance indicators